The Impact of mothers' education on maternal health seeking practices in Uganda - KIM, Se In (KDI School, 2017)
In 1997, Uganda introduced the Universal Primary Education policy, making primary schooling free and expanding people’s access to education. The primary purpose of this study is to examine how the education affects mothers’health seeking behaviors by taking a close look at the utilization of health services by women throughout their pregnancy. To investigate this question, the author utilizes Demographic and Health Surveys of Uganda in 2000/2001, 2006 and 2011,and adopts the method of instrumental variables(IV) by exploiting mothers’age of 1997 as an instrument. The study finds that primary education increases the probability of women seeking health services by 5.5%, use of contraceptive methods by 38.2%, and delivery in hospital by 90.6%. It was found that a year rise in schooling generates statistically significant impact on above the three factors as well. However, there is little evidence other health seeking practices such as the utilization of antenatal care services, are mainly impacted by the level of primary education. Such result implies that though there is a positive but somewhat limited correlation between schoolingand health seeking behavior in Uganda’s context.
Thesis(Master) --KDI School:Master of Public Policy,2017